Post-rehabilitation gingival health with zirconia crowns in deciduous teeth - Calle-Sánchez, María José (2020)
In recent years, aesthetic alternatives to preformed metal crowns have been developed due to the high demand on the part of parents to provide their children with restorations that give natural appearance to deciduous teeth. The present study describes the cases of 3 preschool children whose pieces were rehabilitated with zirconia crowns. They were followed up in the short term, where the evaluation of the gingival index (GI), plaque index (PI), marginal adaptation (AM) and IHOS, for the evaluation of gingival health and oral hygiene was considered. It was found that the preformed zirconia crowns allowed the recovery and preservation of the health of the gingival tissues of the children evaluated.